ZD7288, a blocker of the HCN channel family, increases doubling time of mouse embryonic stem cells and modulates differentiation outcomes in a context-dependent manner - Omelyanenko, Anna; Sekyrova, Petra; Andäng, Michael (SpringerPlus, 2016)
Pluripotent stem cells are the starting cell type of choice for the development of many cell-based regenerative therapies due to their rapid and unlimited proliferation and broad differentiation potential. The unique pluripotent cell cycle underlies both these properties. Hyperpolarization-activated cyclic nucleotide-gated cation (HCN) family channels have previously been reported to modulate mouse embryonic stem cell (ESC) proliferation and here we characterize the effects of HCN inhibitor ZD7288 on ESC proliferation and stem cell identity. The doubling time of cells treated with the HCN blocker increased by ~30 % due to longer G1 and S phases, resulting in a nearly twofold reduction in ESC numbers after 4 day serum-free culture. Slower progression through S phase was not accompanied by H2AX phosphorylation or cell stalling at transition points, although EdU incorporation in treated cells was reduced. Despite the drastic cell cycle perturbations, the pluripotent status of the cells was not compromised by treatment. Cultures treated with the HCN blocker in maintenance conditions maintained pluripotency marker expression on both RNA and protein level, although we observed a reversible effect on morphology and colony formation frequency. Addition of ZD7288 in differentiating media improved FBS-driven differentiation, but not directed differentiation to neuroectoderm, further indicating that altered cell cycle structure does not necessarily compromise pluripotency and drive ESCs to differentiation. The categorically different outcomes of ZD7288 use during differentiation indicate that cell culture context can be determinative for effects of ion-modulatory molecules and underscores the need for exploring their action in serum-free conditions demanded by potential clinical use.
Keywords: Serum; Ion channel modulator; Proliferation; Differentiation; ZD7288; Pluripotency; Embryonic stem cells; Cell cycle